Seismic performance of a multipurpose hall building using nonlinear static analysis - Ruiz–Pico, A. (2024)
The nonlinear static analysis method has facilitated models that are closer to the structural response for strong seismic movements. Therefore, a seismic performance evaluation of a multi-purpose hall building located in a national public university in Chiclayo, Peru, was developed, applying the nonlinear static analysis. This building comprises two similar modules, each with 3 levels and irregular plans. The building's structural system consists of load-bearing walls. It was constructed in 2010 and designed according to E.030 (the Peruvian seismic-resistant standard) and Peru's seismic microzonation. For practical purposes, considering the symmetry of the overall structure, one of the modules was evaluated using nonlinear methods capable of simulating the effect of earthquakes. This development included applying a linear analysis to establish the response spectra and, based on that, performing the nonlinear Pushover analysis. Based on the results, the performance in both directions was determined, considering the performance levels of HAZUS and VISION 2000. The results show that the building has a performance of "Life Safety" and "Near Collapse" in the X and Y directions, respectively. Additionally, the drifts show a close relationship with the performance data, as HAZUS demonstrates that the drifts in the Y direction are not favorable. Therefore, it was determined that structural reinforcement of the building is necessary to improve its unfavorable behavior.